Readily Available Chiral Benzimidazoles-Derived Guanidines as Organocatalysts in the Asymmetric α-Amination of 1,3-Dicarbonyl Compounds - Benavent, Llorenç (Molecules, 2017)
The synthesis and the evaluation as organocatalysts of new chiral guanidines derived from benzimidazoles in the enantioselective α-amination of 1,3-dicarbonyl compounds using di-t-butylazodicarboxylate as aminating agent is herein disclosed. The catalysts are readily synthesized through the reaction of 2-chlorobezimidazole and a chiral amine in moderate-to-good yields. Among all of them, those derived from (R)-1-phenylethan-1-amine (1) and (S)-1-(2-naphthyl)ethan-1-amine (3) turned out to be the most efficient for such asymmetric transformation, rendering good-to-high yields and moderate-to-good enantioselectivities for the amination products.